2023
DOI: 10.1186/s13063-023-07142-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the recruitment of disabled people to clinical trials: a scoping review

Abstract: Introduction Underrepresentation of disabled groups in clinical trials results in an inadequate evidence base for their clinical care, which drives health inequalities. This study aims to review and map the potential barriers and facilitators to the recruitment of disabled people in clinical trials to identify knowledge gaps and areas for further extensive research. The review addresses the question: ‘What are the barriers and facilitators to recruitment of disabled people to clinical trials?’.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…Finally, a challenge that is not unique to pediatric research is the recruitment and engagement of traditionally underrepresented groups, such as individuals with disabilities and racial and ethnic minority populations [ 27 ]. Individuals with disabilities are routinely underrepresented in research because of physical, cognitive, and economic challenges and the added resources that may be required to accommodate their needs [ 28 , 29 ]. For racial and ethnic minority communities, studies have shown that it is important to employ a range of community engagement strategies [ 30 , 31 ], as well as communicate both their unique contributions to research and the benefits conferred with their participation [ 32 34 ].…”
Section: Recruitment Of Vulnerable Populationsmentioning
confidence: 99%
“…Finally, a challenge that is not unique to pediatric research is the recruitment and engagement of traditionally underrepresented groups, such as individuals with disabilities and racial and ethnic minority populations [ 27 ]. Individuals with disabilities are routinely underrepresented in research because of physical, cognitive, and economic challenges and the added resources that may be required to accommodate their needs [ 28 , 29 ]. For racial and ethnic minority communities, studies have shown that it is important to employ a range of community engagement strategies [ 30 , 31 ], as well as communicate both their unique contributions to research and the benefits conferred with their participation [ 32 34 ].…”
Section: Recruitment Of Vulnerable Populationsmentioning
confidence: 99%
“…The clinical study of tongue muscle function and swallowing disorders in adults with DS has some logistical limitations. These include limited geographical availability and capacities of specialized multidisciplinary clinical care centers for DS, which creates barriers for some adults with DS to receive health care services aligned with best practices (45,46), accessibility barriers that disproportionately disenfranchise individuals with communication support needs who may require special accommodation in order to communicate with medical providers (47), which may be applicable to many individuals with DS (44,48,49), and risks for disconnects between researcher expectations and the lived experiences of some disabled study participants (50). In light of these systemic challenges, the continued use of animal models of DS for basic discovery of underlying mechanisms of dysphagia is one of many strategies that can be used to ultimately advance more equitable inclusion of people with DS in the benefits of basic dysphagia research.…”
Section: Discussionmentioning
confidence: 99%
“…Another barrier to participation is the presence of ambiguous eligibility criteria, such as the lack of clearly justified criteria for individuals with conditions that may put participants at risk during the trial. This ambiguity may not adequately account for the diverse range of disabilities among participants in clinical trials [44]. This has been discussed in many previous studies and is a very complex topic that has not yet reached a consensus on the implementation of standardised practice [45][46][47].…”
Section: Discussionmentioning
confidence: 99%
“…Although the challenges faced by under-served groups participating in clinical trials have been investigated internationally, research focusing on disabled people in this context is still limited. Most of the evidence currently available is from researcher perspectives, literature reviews or primary quantitative studies [22][23][24][32][33][34]. The perspectives of carers and disabled people themselves are rarely represented in the research outputs.…”
Section: Introductionmentioning
confidence: 99%